PTU-083 Use Of Polymerase Chain Reaction To Detect Mucosal Cytomegalovirus Infection In Patients With Acute Ulcerative Colitis. (9th June 2014) - Tun, GSZ; Wright, A; Robinson, K; Sidhu, R; Hopper, A; Sanders, DS; McAlindon, M; Raza, M; Lobo, A
Abstract : Introduction: Mucosal CMV infection may complicate acute ulcerative colitis (UC), though the significance remains uncertain. The European Crohn's and Colitis Organisation recommend tissue PCR or immunohistochemistry for CMV detection. The aim of this study was to review experience of assessing patients attending a single unit with acute UC for CMV infection. Methods: A policy of biopsy for CMV infection was adopted for people with acute severe UC admitted to hospital (n = 37) or deteriorating symptoms as an out-patient (n = 8) from 2011–2013. Clinical severity was measured by Mayo score and endoscopic activity by Baron score. Biopsies were assessed for CMV viral DNA by realtime PCR. Serum IgG and IgM antibodies to CMV were measured by chemiluminescence. Results: Biopsies were obtained from 45 patients with UC. 13/45 (28.9%) were positive for CMV DNA (median titre 34900; range 776–1540000 copies/ml). 9/13 (69.2%) CMV PCR positive (+) patients were steroid refractory compared to 14/32 (43.8%) CMV PCR negative (-) p = 0.12. Median Day 3 Mayo scores were 8 for the CMV+ group and 6 for the CMV- group (p = 0.59). Of IPs biopsied up to Day 1 of IV steroids (range -4–1), 6/22 were CMV+ and from Day 2 (median 6; 2–19), 5/20 were CMV+ (p = 0.96). Median cumulative steroid dose prior to biopsy was 0.28 g prednisolone equivalent for CMV+ patients and 0.39 g for CMV- patients (p = 0.51). 3/13 CMV+ patients had had prednisolone ≥10 mg/day for > 14 days prior to biopsy and 11/32 CMV- patients (p = 0.46). No biopsies contained typical histological features of CMV infection. Mayo and Baron scores did not differ between CMV+ and CMV- patients. Mucosal CMV DNA titre in CMV+ patients did not correlate with Baron or Mayo scores. Of the mucosal CMV+ patients, 8/8 tested (100%) were anti-CMV IgG positive with 0/7 IgM positive. Peripheral blood CMV PCR was positive in 10/13 in the biopsy PCR+ group and 0/7 in those biopsy PCR- (sensitivity 60%, specificity 100%). 12/13 CMV PCR+ patients were treated with ganciclovir. 11/13 (84.6%) achieved remission. 2/13 (15.3%) CMV+ and 2/32 (6.2%) CMV- required colectomy (p = 0.33). All 6 patients treated concomitantly with Infliximab and ganciclovir responded fully. Conclusion: PCR of mucosal biopsies detects CMV infection due to viral reactivation in almost a third of patients with deteriorating or acute severe UC. No relationship was demonstrated between CMV infection and disease severity, response to treatment or prior steroid use. Treatment with anti-TNF agents was administered safely in combination with anti-viral drugs. Disclosure of Interest: None Declared.